Evaluation of polyherbal formulation in broilers fed high energy diet: Implications on zootechnical parameters, fat accretion, and serum L-carnitine levels - D’souza, Prashanth; Selvam, Ramasamy (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The current broiler trial was planned to assess the effects of Kolin Plus™, a polyherbal formulation (PHF), on performance, protein and fat accretion, and serum L-carnitine (LC) levels in broilers fed a high-energy diet (HED). Materials and Methods: A total of 500 1-day-old Cobb 430 male chicks were assigned to 5 treatment groups consisting of 10 replicates, with 10 birds in each replicate (n = 100). Group G1 was a negative control fed HED, and group G2, a positive control supplemented with synthetic choline chloride (SCC) 1,500 gm/ton in HED. Groups G3, G4, and G5 were supplemented with PHF in HED at 400, 500, and 750 gm/ton feed, respectively (PHF400, PHF500, and PHF750). Results: The PHF produced a dose-dependent numerical improvement in body weight, feed conversion ratio, livability, and the European Production Index. There were no changes in carcass nitrogen and protein accretion, whereas a statistically significant decrease (p < 0.05) in carcass fat and fat accretion was observed in the SCC and PHF groups. Moreover, PHF showed a significant increase in serum LC levels. Conclusion: Kolin Plus™ improves performance parameters akin to SCC by improving fat metabolism and mobilization by enhancing serum LC levels and restoring normal fat accretion. J. Adv. Vet. Anim. Res., 9(1): 166–174, March 2022 http://doi.org/10.5455/javar.2022.i581